Perancangan Aplikasi Penyusun Jadwal Berbasis Web Menggunakan Algoritma Semut Pada SMA Khalifa IMS Tangerang Selatan - Rahmat Yudha; Ari Mulyoto (CV. Multi Kreasi Media, 2024)
The design of a Web-based scheduling application using the ant algorithm is able to provide an alternative solution for preparing schedules that want a certain time optimally. In this research, the method used is the system development life cycle method (the waterfall paradigm). This method consists of various stages, namely needs analysis, system design, and program writing. From the results of the analysis, it was found: The application of a web-based scheduling application using the ant algorithm, can help prepare schedules quickly and easily while avoiding clashes in scheduling. On the other hand, the process of preparing a schedule using the ant algorithm method can shorten the processing time.